(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Over the last four decades, magic realism has emerged as an international literary phenomenon. It has been acknowledged and adopted as the most influential and effective narrative mode of fiction writing by the writers and critics across the world. It was Latin America where magic realism got its identity and became the most famous literary mode but, it has now developed its deviations in different geographical and cultural contexts. Now, it is no longer a narrative mode but a way of thinking. Therefore, it can not remain confined to a particular geographical location. It migrated from its starting point Germany to Latin America and from Latin America to various cultural shores around the world. It flourished more rapidly especially in the postcolonial countries. Today, magic realism enjoys a global popularity through the works of master exponents of this genre from various parts of the world such as Gunter Grass from Germany, Salman Rushdie from India, Ben Okri from Nigeria Angela Carter from England among others.